2010
DOI: 10.1088/0957-4484/21/49/495702
|View full text |Cite
|
Sign up to set email alerts
|

Emitter spacing effects on field emission properties of laser-treated single-walled carbon nanotube buckypapers

Abstract: Carbon nanotube (CNT) emitters on buckypaper were activated by laser treatment and their field emission properties were investigated. The pristine buckypapers and CNT emitters' height, diameter, and spacing were characterized through optical analysis. The emitter spacing directly impacted the emission results when the laser power and treatment times were fixed. The increasing emitter density increased the enhanced field emission current and luminance. However, a continuous and excessive increase of emitter den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fibers consisting of CNTs have been used in SHM of damage in structures due to their excellent mechanical behavior, flexibility, and deformation sensitivity [40]- [43]. To have excellent conductivity, CNTs are usually implemented in well-aligned free-standing or a conductive membrane (sheet) of randomly oriented CNTs named as bucky paper [44]- [50]. However, several studies showed that oriented and CNTs grown on a specific substrate required critical control on the fabrication process to ensure better dimension and spacing of CNTs [51]- [53].…”
Section: Introductionmentioning
confidence: 99%
“…Fibers consisting of CNTs have been used in SHM of damage in structures due to their excellent mechanical behavior, flexibility, and deformation sensitivity [40]- [43]. To have excellent conductivity, CNTs are usually implemented in well-aligned free-standing or a conductive membrane (sheet) of randomly oriented CNTs named as bucky paper [44]- [50]. However, several studies showed that oriented and CNTs grown on a specific substrate required critical control on the fabrication process to ensure better dimension and spacing of CNTs [51]- [53].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, CNT based field emitters are used in vacuum electronics to produce electron sources [2], flat panels [3], X-ray sources [4,5], and microwave amplifiers [6], exploiting a low-threshold electric field and large emission current density. To increase the extracted current, CNT arrays are usually implemented [7,8] as free-standing well-aligned CNTs [9][10][11] or paper-like sheet of randomly oriented CNTs, named buckypaper [12,13].…”
Section: Introductionmentioning
confidence: 99%